2010
DOI: 10.1210/jc.2010-0757
|View full text |Cite
|
Sign up to set email alerts
|

Rising Serum 25-Hydroxy-Vitamin D Levels after Weight Loss in Obese Women Correlate with Improvement in Insulin Resistance

Abstract: Blood 25OHD levels were low in obese women and correlated inversely with severity measures of obesity. Weight loss of 10% after low-calorie diet increased 25OHD levels, and this increase was mainly associated with improvement of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
87
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 41 publications
10
87
2
4
Order By: Relevance
“…Similar findings were reported by others after diet and/or exerciseinduced weight loss. 9,10,12 These findings are in agreement with the hypothesis that VD is being stored in the AT 24,26 and confirm previous data on how plasma 25OHD depends on the volume of distribution. 23 The increase in 25OHD fits very well with the observed increased expression of the degrading enzyme, the 24-hydroxylase CYP24A1, as CYP24A1 expression is induced by 1,25-OH 2 D. 36,37 As CYP24A1 degrades both 25OHD and 1,25(OH) 2 D, these findings suggest a higher turnover of both 25OHD and 1,25(OH) 2 D following weight loss.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings were reported by others after diet and/or exerciseinduced weight loss. 9,10,12 These findings are in agreement with the hypothesis that VD is being stored in the AT 24,26 and confirm previous data on how plasma 25OHD depends on the volume of distribution. 23 The increase in 25OHD fits very well with the observed increased expression of the degrading enzyme, the 24-hydroxylase CYP24A1, as CYP24A1 expression is induced by 1,25-OH 2 D. 36,37 As CYP24A1 degrades both 25OHD and 1,25(OH) 2 D, these findings suggest a higher turnover of both 25OHD and 1,25(OH) 2 D following weight loss.…”
Section: Discussionsupporting
confidence: 91%
“…However, results are inconsistent. After diet-and exercise-induced weight loss, both increased [9][10][11] and unaltered 12,13 circulating levels of 25OHD have been reported. Likewise, after major weight loss by bariatric surgery, both temporary [14][15][16] and long-term increases [16][17][18] in circulating levels of 25OHD have been reported, along with reports of no changes one year after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The demonstrated inverse relationship between BMI and vitamin D status has been established in earlier reports (48,49). It has been shown that in obese individuals a higher proportion of vitamin D, which is fat soluble, is sequestered in adipose tissue and thereby the bioavailability of vitamin D is low.…”
Section: Discussionmentioning
confidence: 67%
“…The observation that obesity is associated with below-normal serum 25-hydroxyvitamin D concentrations and/or overt deficiency is not new; however, as obesity prevalence has grown, so have the number of reports in the literature regarding this phenomenon. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Some of the most recent information about low vitamin D status and obesity comes from studies in bariatric surgery patients, reporting low preoperative circulating levels of 25-hydroxyvitamin D. [21][22][23][24][25][26][27][33][34][35][36][37][38] In fact, a recent systematic review of 14 studies with about 1500 patients undergoing bariatric surgical procedures confirmed that obese individuals have serum 25-hydroxyvitamin D levels below 80 nmol l À1 preoperatively. 39 Other investigators have reported that body mass index (BMI) 25,26,[40][41][42][43][44][45][46] and body fat 20,45,…”
Section: Methodsmentioning
confidence: 99%
“…They reported an initial increase (at 6 weeks and 6 months after surgery) in serum 25-hydroxyvitamin D concentrations, which declined toward baseline by 1 year after RYGB. Tzotzas et al 66 reported that serum 25-hydroxyvitamin D concentrations increased with nonbariatric surgery-induced weight loss. Taken together, these studies provide some level of support for the notion that adipose tissue could be sequestering vitamin D, and that, at least during the early phases of weight loss, it is possible that vitamin D may be released into circulation.…”
Section: Methodsmentioning
confidence: 99%